A review of machine tool accuracy enhancement through error compensation in serial and parallel kinematic machines. (17th February 2010) - Mekid, Samir; Ogedengbe, Tunde
The accuracy of machine tools is a critical factor that affects the quality of manufactured products which is one of the most important considerations for any manufacturer. The consistent performance of the machine tool is constrained by the errors built in the machine (e.g., assembly error) or occurring on a periodic basis on the account of change in temperature and cutting forces. A number of studies have been conducted to identify, predict and compensate these errors to improve machine tools accuracy. This paper reviews these studies extensively and identifies the issues and challenges for machine tool accuracy enhancement leading to zero defects parts.